Clinical activity of checkpoint inhibitors in angiosarcoma: A retrospective cohort study. Issue 18 (6th July 2022) - Ravi, Vinod; Subramaniam, Aparna; Zheng, Jing; Amini, Behrang; Trinh, Van A.; Joseph, Jocelyn; Mennel, Robert G.; Bishop, Andrew J.; Sturgis, Erich M.; Goepfert, Ryan P.; Yalamanchili, Sudha; Botello, Gilberto; et al.
Abstract : Background: Systemic treatments for angiosarcoma remains an area of unmet clinical need. The authors conducted this retrospective study to assess the clinical activity of checkpoint inhibitors in patients with angiosarcoma. The primary objective was to assess the objective response rate, and the secondary objective was to assess the progression‐free and overall survival durations and disease control rate. Methods: Patient data were obtained using The University of Texas MD Anderson Cancer Center Tumor Registry database. The final study population was refined to only include patients who had undergone pembrolizumab monotherapy. The objective response rate was evaluated using RECIST/irRECIST version 1.1. Progression‐free survival and overall survival were defined as the time from the initiation of immunotherapy to disease progression or recurrence, death, or last follow‐up and to death or last follow‐up, respectively. Results: The final cohort comprised 25 patients. Most patients had metastatic disease (72%) and had undergone at least two lines of systemic therapy (80%) before starting pembrolizumab. The objective response rate was 18%, whereas the disease control rate was 59%. The median progression‐free survival duration was 6.2 months and was not significantly different between the cutaneous (4.7 months) and visceral angiosarcoma (6.2 months) groups ( p  = .42). The median overall survival duration was 72.6 months. Toxicities were recorded for eight patients, with fatigue, anemia, constipation, and rash being the most common. Conclusions: Pembrolizumab shows durable clinical activity in angiosarcoma. These findings suggest that checkpoint inhibition as monotherapy or combination therapy is likely to have a high probability of success.© 2022 American Cancer Society. Lay summary: This is the largest retrospective study to assess the clinical activity of checkpoint inhibitor monotherapy in angiosarcomas. The study includes an adequate number of patients with visceral angiosarcoma that enabled to obtain meaningful clinical insights that were previously unavailable. Our findings indicate an improvement in progression‐free survival with pembrolizumab that is comparable to other active agents in angiosarcoma. Pembrolizumab monotherapy in angiosarcomas also has a favorable tolerability profile. Our findings emphasize the need for prospective studies to evaluate the activity of pembrolizumab monotherapy and combination therapy. Abstract : The key finding in this study is that median progression‐free survival and median overall survival in this cohort was considerably longer than what has been reported in the literature previously. Pembrolizumab monotherapy is active in angiosarcomas with a favorable tolerability profile.